Exploring the active chemical compounds and pharmacological effects of Artemisia Argyi leaves through commonality, authenticity and aging - Boyu Chen; Jiaxin Liu; Xu Dai; Lufan Xu; Wenying Cui; Rouan Chen; Tian Lan; Yiider Tseng (Phytomedicine Plus)
Background: Artemisia argyi (A. argyi), a pivotal herb extensively used in moxibustion therapy, has long been widely recognized in Traditional Chinese Medicine (TCM) for its significant clinical efficacy. Since the therapeutic effects of a drug are inherently linked to its chemical composition, the identification of potential active compounds in A. argyi leaves becomes one of the priorities for continuously advancing moxibustion. Purpose: Hence, this study aims to extract key bioactive compounds contributing to its medicinal properties by performing data mining from literature. Three criteria, commonality, authenticity and aging, are applied to identify the common compounds across different regions; the superior compounds unique to the authentic Qichun A. argyi leaves; and the distinctive compounds emerging during the aging process. Methods: Data-driven approaches, which have been developed through decades of literature mining, are grounded in conventional evaluation principles of commonality, authenticity, and aging. The therapeutic effects of bioactive compounds have been verified using 3 individual rheumatoid arthritis (RA)-associated primary fibroblast-like synovial cells (FLS) with 3 times. The anti-proliferative effects were assessed utilizing the CCK-8 assay and the real-time cell analysis (RTCA) system. In addition, the anti-invasive effects were also evaluated through RTCA, while the anti-inflammatory effects were investigated using enzyme-linked immunosorbent assays (ELISA). Results: Our work highlights the potential key functional compounds of A. argyi leaves, including volatile substances, including 1,8-Cineole, β-Caryophyllene, p-Cymene and Caryophyllene oxide, as well as non-volatile compounds, including Eupatilin, Isochlorogenic acid C, Isochlorogenic acid A, and Vitexin. We further validated the anti-proliferative, anti-invasive and anti-inflammatory effects of these compounds on RA-FLS in vitro, demonstrating their therapeutic potential in RA. Conclusion: This approach, established by three criteria, commonality, authenticity and aging, has identify bioactive compounds in A. argyi that may play a therapeutic role by altering the pathologic phenotype of cells. This study provides insights towards pharmacological research of A. argyi and elucidates unknown therapeutic mechanisms against RA.